HAPPINESS OF PREGNANT WOMEN AND CHILDREN'S ACADEMIC ACHIEVEMENTS VALUE IN KINDERGARTEN KHADIJAH - Dian Lestari Hidayah; Nining Febriyana; Atika Atika (Indonesian Midwifery and Health Sciences Journal, 2021)
Background: Indonesia's education ranked sixth bottom of the 2018 world rankings compiled by the Program for International Student Assessment (PISA). The value of academic achievement is an indicator of the quality of students in the academic field. One of the factors that influence achievement is children's intelligence. Child's intelligence is influenced by the happiness of his mother during pregnancy. This study aims to analyze the relationship between the happiness of pregnant women and the value of children's academic achievement in TK Khadijah Gedangan. Method: This type of research is an observational analytic study, using a cross sectional approach. The study population was all TK-A and TK-B students at TK Khadijah Gedangan and their biological mothers. The total sampling method was carried out according to the inclusion criteria and exclusion criteria. Collecting data using a demographic questionnaire and OHQ which was translated into Indonesian. SPSS software was used to test the Spearman rank correlation statistical test. Result: Obtained N = 54, significance value 0.514, correlation coefficient value -.091. Conclusion: The happiness of pregnant women is not related to the achievement scores of kindergarten children.Keywords: happiness, pregnant women, academic achievement